Effects of sodium bicarbonate and magnesium oxide as buffers on milk production in dairy cows - Derya Umucalılar; Erdoğan Şeker (Eurasian Journal of Veterinary Sciences)
In experiment, 16 dairy cows were divided into three groups. Five of them used as control group, five of them used in 1 % NaHC03 group and rest of them were placed in third group and 0.5 % MgO was added to the teed. End of the experiment, the milk production in the NaHC03 group (22.60 kg/day) was decreased compared to the MgO (23.75 kg/day) and control groups (24.5 kg/day) Average dry matter intakes were found 16.23, 13.52 and 13.65 kg/day. respectively. And by addition of buffers milk production was reduced significantly (P<0.05). In the case of 3.5 and 4 % fat corrected milk were not significantly difference (P>0.05). Among the research period, there was no significant (P>0.05) difference between the miik samples ol the groups in fat, protein, lactose, ash, dry malter and non -fat dry matter values which were determined weekly. It was determined that NaHC03 was decreased daily milk protein and lactose yield and buffers were significantly decreased non-fat dry matter yield and dry matter consumption (P<0.05), The buffers caused an increase in the costs of the rations, but they reduced the feed consumption. Because of the decreasing in the feed consumption they supplied on advantage in expences ol i kg milk, milk fat. milk protein and non-fat dry malter At the end of the research it was determined that the buffers caused decreasing the amount of average milk production. However the bullers caused an increase of average milk fat ratio. Magnesium oxide as buffers found more effective lhan sodium bicarbonate on milk production and composition As a result, it is considered usetul that the buffers used in feeding high milk producing dairy cows which do not consume enough amount of high quality lorage in their rations.